ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN DI BEI PERIODE 2008-2013) - Prasetyo, Rifky; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2016)
Corporate value is very important especially for those companies go public. Corporate value can be reflected through the stock market price. The higher the price the higher the stock market value of the company. In the long term, the company's goal is to optimize company’s value. Based on previous research, there is research gap on what factors that affecting corporate value at the corporate minning. The aim of this study was to analyze factors affecting company’s value at a mining company listed on the Indonesia Stock Exchange in 2009-2014.The study population was all financial data of companies listed on the Indonesia Stock Exchange in 2009-2014. The sampling method used in this research is purposive sampling method. The sample used in this study is a mining company listed on the Indonesia Stock Exchange in 2009-2014. The analysis technique used is multiple linear regression analysis.Based on the results ROA and DER positively influence company’s value while NPM, DPR and firm size does not affect company’s value. Based Adjusted R Square, the coefficient of determination of this study is 0.231, this means that the variations in company’s value can be explained by the independent variable by 23.1%.